Elastin-like hydrogel stimulates angiogenesis in a severe model of critical limb ischemia (CLI): An insight into the glyco-host response. (February 2021) - Marsico, Grazia; Jin, Chunseng; Abbah, Sunny A.; Brauchle, Eva M.; Thomas, Dilip; Rebelo, Ana Lúcia; Orbanić, Doriana; Chantepie, Sandrine; Contessotto, Paolo; Papy-Garcia, Dulce; Rodriguez-Cabello, Carlos; Kilcoyne, Michelle; et al.
Abstract: Critical limb ischemia (CLI) is characterized by the impairment of microcirculation, necrosis and inflammation of the muscular tissue. Although the role of glycans in mediating inflammation has been reported, changes in the glycosylation following muscle ischemia remains poorly understood. Here, a murine CLI model was used to show the increase of high mannose, α-(2, 6)-sialic acid and the decrease of hybrid and bisected N-glycans as glycosylation associated with the ischemic environment. Using this model, the efficacy of an elastin-like recombinamers (ELR) hydrogel was assessed. The hydrogel modulates key angiogenic signaling pathways, resulting in capillary formation, and ECM remodeling. Arterioles formation, reduction of fibrosis and anti-inflammatory macrophage polarization wa also induced by the hydrogel administration. Modulation of glycosylation was observed, suggesting, in particular, a role for mannosylation and sialylation in the mediation of tissue repair. Our study elucidates the angiogenic potential of the ELR hydrogel for CLI applications and identifies glycosylation alterations as potential new therapeutic targets.